TRANSFORMATIVE POTENTIAL OF THE POETIC UTTERANCE: CRITICISM OF PRAGMATIC POETICS - Selishcheva, Dariia V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2018)
Taking into account the democratization of writing and the mutual imposition of discourses in the modern media environment, the poetic attitude to language is perceived as a possible way of developing an understanding of the meaning of the word, understanding the language not as a transparent medium, but as an active thinking environment. Such an approach is possible thanks to a rethinking of the phenomenon of poetry based on the ideas of the pragmatic poetics of P. Arsenyev. Debunking the romantic idea of the poet as a medium between God and the reader, as well as criticizing J. Austin’s idea of language as a means of influencing another, P. Arsenyev, nevertheless, considers poetic utterance as a method of political influence on the listener, which limits the space of existential opportunities, opened by this utterance. The concept of the poetic act as a way of opening the language, which is developed by the author based on the philosophy of the language of M. Heidegger and F.-V. von Herrmann, attempts to develop an appropriate understanding of poetry and circumvent the limitations of the concept of pragmatic poetics. The author analyzes the approach of P. Arsenyev to the interpretation of L. N. Tolstoy’s “Confession”. The conclusion is made about the inconsistency of the authors’ approach: on the one hand, the text of the “Confession” is viewed from the point of view of the pragmatics of its impact on the reader, which involves the reader’s subjectivation as a moral judge, sentencing the author. On the other hand, the very fact that P. Arsenyev reads “Confession” not from a moralistic, but from a philosophical and linguistic point of view, suggests that the explanation of the existential-transformative potential of the latter cannot be reduced only to indication of its immediate pragmatic context. The development of the terminology of existential analytics of Dasein is carried out by extrapolating Heidegger’s terminology to the situation of a poetic act, understood as a two-stage event (Ereignis) of understanding, which is a cultural phenomenon.